Building structures - Ambrose, James E.; Tripeny, Patrick (Hoboken, N.J. : Wiley, 2012)
"This new edition continues its legacy as the reference of choice for architects studying contemporary issues and design practices for building structures by taking a conceptual approach that foregos complicated mathematics. Looking at the role of the structure as a building subsystem, it offers the fundamentals of computational methods for design of wood, steel, and reinforced concrete structures, along with new material such as discussion of the LRFD method of design. Profusely illustrated with new case studies, this go-to guide is perfect for non-engineers to understand and visualize structural design"--
Machine generated contents note: Preface.Introduction.Chapter 1. Basic Concepts.1.1 Basic Concerns.1.2 Architectural Considerations.1.3 Structural Functions.1.4 Structural Materials.1.5 Structural Systems.Chapter 2. Investigation of Structures.2.1 Introduction to Structural Investigation.2.2 Static Forces.2.3 Stresses and Strains.2.4 Special Topics.2.5 Dynamic Behavior.Chapter 3. Structural Elements.3.1 Beams.3.2 Tension Elements.3.3 Compression Elements.3.4 Trusses.3.5 Rigid Frames.3.6 Special Structures.Chapter 4. Wood Structures.4.1 General Concerns for Wood.4.2 Wood Products and Systems.4.3 Design Data for Structural Lumber.4.4 Wood Spanning Systems.4.5 Wood Trusses.4.6 Wood Columns.4.7 Fasteners and Connections for Wood.Chapter 5. Steel Structures.5.1 General Concerns for Steel.5.2 Steel Beams, Joists, and Decks.5.3 Steel Columns.5.4 Bolted Connections for Steel Structures.5.5 Steel Trusses.Chapter 6. Concrete Structures.6.1 General Concerns for Concrete.6.2 Reinforced Concrete Flexural Members.6.3 Concrete Columns.6.4 Concrete Foundations.Chapter 7. Masonry Structures.7.1 General Concerns for Masonry.7.2 Structural Masonry.7.3 Masonry with Concrete Units.7.4 Form and Classification of Compression Elements.7.5 Brick Masonry.7.6 Miscellaneous Masonry Construction.Chapter 8. Building Foundations and Site Structures.8.1 General Considerations.8.2 Soil Properties and Foundation Behavior.8.3 Shallow Bearing Foundations.8.4 Elements of Foundation Systems.8.5 Deep Foundations.8.6 Special Problems and Construction.Chapter 9. Lateral Force Effects.9.1 General Concerns for Lateral Effects.9.2 Wind Effects on Buildings.9.3 Earthquake Effects on Buildings.9.4 Elements of Lateral Resistive Systems.Chapter 10. Building Structures Design Examples.10.1 General Concerns for Structures Design.10.2 Building One.10.3 Building Two.10.4 Building Three.10.5 Building Four.10.6 Building Five.10.7 Building Six.10.8 Building Seven.10.9 Building Eight.10.10 Building Nine.Appendix A. Properties of Sections.Appendix B. Glossary.Appendix C. Exercise Problems.Appendix D. Study Aids.References.Index. .
Includes bibliographical references (p. 519) and index.
Keywords: Structural design; Structural analysis (Engineering); ARCHITECTURE / Design, Drafting, Drawing & Presentation